The Determinants of Travel Agency Client Loyalty - Michalska-Dudek, Izabela (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article presents the results of the author’s research identifying the key determinants of loyalty among travel agency clients. It also develops a profile of a loyal customer of travel agency services. The analysis covers real historical data, taken from the accounting and booking system of one nationwide franchise of networks in Poland consolidating 60 agency offices and referring to 15,248 reservations made in the years 2013–2017 by clients who purchased tourist services. A non-parametric method of artificial neural networks was applied, while the most important determinants of behavioural loyalty were the following variables: the duration of the tour, the number of children under the age of 14 included in the booking, the price and the destination of the tourist event.